Loss of function mutation in Ank causes aberrant mineralization and acquisition of osteoblast-like-phenotype by the cells of the intervertebral disc - Takashi Ohnishi; Victoria Tran; Kimheak Sao; Pranay Ramteke; William Querido; Ruteja A. Barve; Koen van de Wetering; Makarand V. Risbud (Cell Death and Disease, 2023)
Abstract Pathological mineralization of intervertebral disc is debilitating and painful and linked to disc degeneration in a subset of human patients. An adenosine triphosphate efflux transporter, progressive ankylosis (ANK) is a regulator of extracellular inorganic pyrophosphate levels and plays an important role in tissue mineralization. However, the function of ANK in intervertebral disc has not been fully explored. Herein we analyzed the spinal phenotype of Ank mutant mice (ank/ank) with attenuated ANK function. Micro-computed tomography and histological analysis showed that loss of ANK function results in the aberrant annulus fibrosus mineralization and peripheral disc fusions with cranial to caudal progression in the spine. Vertebrae in ank mice exhibit elevated cortical bone mass and increased tissue non-specific alkaline phosphatase-positive endplate chondrocytes with decreased subchondral endplate porosity. The acellular dystrophic mineral inclusions in the annulus fibrosus were localized adjacent to apoptotic cells and cells that acquired osteoblast-like phenotype. Fourier transform infrared spectral imaging showed that the apatite mineral in the outer annulus fibrosus had similar chemical composition to that of vertebral bone. Transcriptomic analysis of annulus fibrosus and nucleus pulposus tissues showed changes in several biological themes with a prominent dysregulation of BMAL1/CLOCK circadian regulation. The present study provides new insights into the role of ANK in the disc tissue compartments and highlights the importance of local inorganic pyrophosphate metabolism in inhibiting the mineralization of this important connective tissue.